Makna Simbolik Tradisi Manganan sebagai Wujud Syukur dan Identitas Budaya Masyarakat - Ramiyati Ramiyati; Argitha Aricindy; Wasino; Tri Astuti (Indo Publishing, 2026)
The Manganan tradition is one of the local wisdoms that continues to be preserved by the people of Banjarjo Village, Padangan District, Bojonegoro Regency. This tradition symbolizes the community’s gratitude for the harvest, safety, and prosperity bestowed by God Almighty. This study aims to explore the symbolic meanings embodied in the Manganan tradition and to understand its role as a cultural identity of the local community. The research employed a qualitative approach with an ethnographic method. Data were collected through observation, in-depth interviews with community leaders and tradition participants, and documentation of the Manganan activities. The findings reveal that each element of the tradition such as offerings, communal prayers, and shared meals contains symbolic meanings reflecting religiosity, togetherness, and gratitude. Furthermore, the Manganan tradition serves as a medium to strengthen social solidarity and maintain the continuity of cultural values across generations. Therefore, Manganan functions not only as a religious ritual but also as a form of cultural identity that reinforces the social cohesion and cultural resilience of the Banjarjo community amid modernization